An Analysis of the Concept of Islamic Thought Renewal: A Comparative Study of the Thought of Hasan Hanafi and Nurcholish Madjid - Firmansyah; Ruslan (Journal of Indonesian Islamic Studies, 2025)
The renewal of Islamic thought seeks to respond to modernity while preserving Islam's foundational values, yet reformist projects differ according to their intellectual and socio-political settings. This study compares Hasan Hanafi's and Nurcholish Madjid's paradigms of Islamic renewal by examining their epistemological foundations, treatment of Islamic tradition, interpretive methods, objectives, and social implications. It employed qualitative comparative library research using selected primary works by both thinkers and relevant secondary scholarship. Data were collected through documentation and close reading, coded into five analytical categories, and examined through descriptive, contextual, and comparative analysis. The findings show that both thinkers reject rigid textualism, regard Islamic tradition as a dynamic resource open to critical reinterpretation, and orient renewal toward human dignity, justice, and social welfare. Their differences lie in methodology and transformative orientation. Hanafi reconstructs Islamic epistemology through phenomenology, anthropocentric theology, and al-Yasar al-Islami, directing renewal toward liberation from colonialism, authoritarianism, and structural inequality. Madjid develops Islamic Neo-Modernism through rationalization, the desacralization of worldly institutions, socio-historical interpretation, and inclusive pluralism, directing renewal toward intellectual, cultural, and democratic transformation. The comparison therefore identifies two distinct but potentially complementary models: Hanafi's revolutionary-structural renewal and Madjid's evolutionary-cultural renewal. This typology clarifies how different reform methodologies can preserve Islamic normativity while responding to diverse modern social contexts.